2000
DOI: 10.1017/s004857720099005x
|View full text |Cite
|
Sign up to set email alerts
|

Mental fatigue and task control: Planning and preparation

Abstract: The effects of mental fatigue on planning and preparation for future actions were examined, using a task switching paradigm. Fatigue was induced by "time on task," with subjects performing a switch task continuously for 2 hr. Subjects had to alternate between tasks on every second trial, so that a new task set was required on every second trial. Manipulations of response-stimulus intervals (RSIs) were used to examine whether subjects prepared themselves for the task change. Behavioral measurements, event-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
162
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(187 citation statements)
references
References 0 publications
19
162
2
4
Order By: Relevance
“…during rumination). 28,29,35,34,41 To conclude, we can state that although the ability of pain to disrupt current performance is already frequently researched, and its function has been variously described as an evolved interrupt forming part of a general defensive system 4,18,40 , further research to clarify under which conditions pain interferes with task performance is still necessary.…”
Section: Discussionmentioning
confidence: 99%
“…during rumination). 28,29,35,34,41 To conclude, we can state that although the ability of pain to disrupt current performance is already frequently researched, and its function has been variously described as an evolved interrupt forming part of a general defensive system 4,18,40 , further research to clarify under which conditions pain interferes with task performance is still necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A task switching paradigm (Lorist et al, 2000) was used, which allows to study the effect of mental fatigue on cognitive control processes involved in the planning and preparation for future actions (Lorist et al, 2000). Mental fatigue refers to the effects that people may experience after or during prolonged periods of demanding cognitive activity and was induced here by two hours of continuous task performance, that is by time on task (Lorist et al, 2000(Lorist et al, , 2005. During task execution subjects were facing a color monitor on which a square (4 × 4 cm) subdivided into four equal quadrants was displayed.…”
Section: Participants and Taskmentioning
confidence: 99%
“…resource exhaustion at a lower level of WM load) in middle-aged adults. Studies utilizing the induced fatigue paradigm (in which elicited fatigue falls under the construct of 'primary fatigue' proposed by DeLuca, 2005b) have shown that higher-level cognitive control functions are particularly sensitive to detrimental induced fatigue effects (Lorist et al, 2000(Lorist et al, , 2005Van der Linden et al, 2003). Furthermore, sustained task performance has been shown to elicit a lasting decrease in cerebral blood flow in the fronto-parietal attention network in association with a fatigue-related reduction in performance (Lim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%